Perceptions of firearms in a cohort of women exposed to intimate partner violence (IPV) in Central Pennsylvania - Laura Leuenberger; Erik Lehman; Jennifer McCall-Hosenfeld (BMC, 2021)
Abstract Background Almost one-half of U.S. women will experience intimate partner violence (IPV), defined as physical, sexual, or psychological harm by a current or former partner. IPV is associated with an increased risk of homicide, with firearms as the most commonly used weapon. We designed this study to better understand the correlation of interpersonal trauma exposures and demographic factors on firearm perceptions among a cohort of IPV-exposed women. Methods Two hundred sixty-seven women in central Pennsylvania with exposure to IPV were surveyed about perceptions of gun access, safety, and gun presence in the home. Trauma variables included IPV type, IPV recency, unwanted sexual exposure, and adverse childhood experiences (ACEs). Multivariable analyses examined three questions examining firearm perceptions controlling for trauma exposures and demographics. Results Ease of firearm acquisition: Women who were older (mean 44.92 years +/− SD 12.05), compared to women who were younger (40.91 +/− SD 11.81 years) were more likely to describe it as easy or very easy to acquire a gun (aOR 1.05, 95%CI 1.004, 1.10). Perceived safety in the proximity of a gun: Women with the highest ACE score were less likely to feel safe with a gun nearby (aOR 0.31, 95%CI 0.14, 0.67). Odds of guns in the home: Women who were divorced or separated (aOR 0.22, 95%CI 0.09, 0.54), women were widowed or single (aOR0.23, 95%CI 0.08, 0.67), and women who were partnered (aOR 0.45 95%CI 0.20, 0.97) had lower odds of having a gun in the home, compared to married women. There was no significant effect of the trauma variables on the odds of having a gun at home. Conclusions Women with more severe childhood trauma felt less safe around firearms, but trauma exposures did not predict the perception of gun prevalence in the local community or gun ownership. Instead, demographic factors of marriage predicted presence of a gun in the home.